Wattles whittle hunger - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
Trees are seen increasingly as a means of stabilizing soils through reforestation and of providing fuelwood and fodder but most have not been seen as a means of improving human nutrition directly. However the knowledge that Australian Aborigines,...